Continuous-Flow Processes for the Production of Floxacin Intermediates: Efficient C-C Bond Formation through a Rapid and Strong Activation of Carboxylic Acids - Shao-Zheng Guo; Zhi-Qun Yu; Wei-Ke Su (Georg Thieme Verlag KG, 2020)
The development of highly efficient C-C bond formation methods for the synthesis of ethyl 2-(2,4-dichloro-5-fluorobenzoyl)-3-(dimethylamino)acrylate 1 in continuous flow processes has been described, which is based on the concept of rapid and efficient activation of carboxylic acid. 2,4-Dichloro-5-fluorobenzoic acid is rapidly converted into highly reactive 2,4-dichloro-5-fluorobenzoyl chloride by treating with inexpensive and less-toxic solid bis(trichloromethyl)carbonate. And then it rapidly reacts with ethyl 3-(dimethylamino)acrylate to afford the desired 1. This process can be performed under mild conditions. Compared with the traditional tank reactor process, less raw material consumption, higher product yield, less reaction time, higher operation safety ensured by more the environmentally friendly procedure, and process continuity are achieved in the continuous-flow system.